City of lies - Thompson, Victoria (Victoria E.) (Thompson, Victoria (Victoria E.). Counterfeit lady novel., 2017)
"An exciting new series featuring woman-on-the-run Elizabeth Miles--from the beloved national bestselling author of the Gaslight Mysteries. Every woman plays a part--but some are more dangerous than others ... Like most women, Elizabeth Miles assumes many roles; unlike most, hers have made her a woman on the run. Living on the edge of society, Elizabeth uses her guile to relieve so-called respectable men of their ill-gotten gains. But brutal and greedy entrepreneur Oscar Thornton is out for blood. He's lost a great deal of money and is not going to forgive a woman for outwitting him. With his thugs hot on her trail, Elizabeth seizes the moment to blend in with a group of women who have an agenda of their own. She never expects to like or understand these privileged women, but she soon comes to respect their intentions, forming an unlikely bond with the wealthy matriarch of the group whose son, Gideon, is the rarest of species--an honest man in a dishonest world. Elizabeth knows she's playing a risky game, and her deception could be revealed at any moment, possibly even by sharp-eyed Gideon. Nor has she been forgotten by Thornton, who's biding his time, waiting to strike. Elizabeth must draw on her wits and every last ounce of courage she possesses to keep her new life from being cut short by this vicious shadow from her past"--